2020
DOI: 10.1038/s41598-020-59057-5
|View full text |Cite
|
Sign up to set email alerts
|

SETD3 acts as a prognostic marker in breast cancer patients and modulates the viability and invasion of breast cancer cells

Abstract: In several carcinomas, the SET Domain Containing 3, Actin Histidine Methyltransferase (SETD3)is associated with oncogenesis. However, there is little knowledge about the role of SETD3 in the progression and prognosis of breast cancer. In this study, we first analyzed the prognostic value of SETD3 in breast cancer patients using the database of the public Kaplan-Meier plotter. Moreover, in vitro assays were performed to assess the role of SETD3 in the viability and capacity of invasion of human breast cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 76 publications
0
32
0
Order By: Relevance
“…Other SETD-domain protein methyltransferases, such as SETD3, have also been considered as therapeutic targets for cancer. For example, it has been reported that SETD3 negatively correlates with prognosis in breast cancers [ 29 ]. However, further clarification is required with regard to the role of this protein in HGSOC.…”
Section: Discussionmentioning
confidence: 99%
“…Other SETD-domain protein methyltransferases, such as SETD3, have also been considered as therapeutic targets for cancer. For example, it has been reported that SETD3 negatively correlates with prognosis in breast cancers [ 29 ]. However, further clarification is required with regard to the role of this protein in HGSOC.…”
Section: Discussionmentioning
confidence: 99%
“…The publically available gene expression database Kaplan‐Meier plotter (KM plotter) (https://kmplot.com) was used to analyze the prognostic value of the hedgehog signaling related‐genes in the relapse‐free survival of breast cancer patients 30 . The establishment of the database of the gene expression data and survival information was performed as were previously described in Espinoza‐Sánchez et al, 23 Hassan et al, 24 and Györffy et al 30 Patients were stratified by ER, progesterone receptor, HER2 expression, and lymph node status, as well as for the molecular classification, and grading. We analyzed the expression of some genes of the Hh pathway and visualized their correlation to survival by generating Kaplan‐Meier survival plots.…”
Section: Methodsmentioning
confidence: 99%
“…For example, we have recently shown that altered expression of the NF-κB pathway and the methyltransferase SETD3 are associated with subtype-specific poor survival of breast cancer patients. 23,24 However, the role of the Hh pathway in the initiation and progression of breast cancer is not well understood. GLI2 and PTCH1 play an important role in the development of the mammary gland in murine models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the prognostic value of UGDH and other functionally linked genes, the online tool kmplot.com [35], which allows a meta-analysis of gene expression in relation to breast cancer patient survival, was employed [36]. Gene expression data was obtained through microarray analysis of widely used arrays of the GEO database and converted into Kaplan-Meier plots.…”
Section: Kaplan-meier Plots and Tcga Expression Datamentioning
confidence: 99%